The Effect of Mahkota Dewa (Phaleria macrocarpa) Pulp Extract by Peroral Administration Toward The Percentage of Capacitation and Acrosome Reaction in Rat (Rattus norvegicus) - Bagyo, Dhanang Estu; Utomo, Budi; Setiabudi, Rudy Sukamto (KnE Life Sciences, 2017)
This research was conducted to find outthe influence of mahkota dewa (Phaleria macrocarpa) pulp extract against the percentage of capacitation and acrosome reaction of male rat (Rattus norvegicus). The experimental animals used are 20 male rats with the average body weight of 200g and were divided into four different groups. P0 group was the control group and given only CMCNa 0.5%. P1, P2,and P3 was given mahkota dewa pulp extract with a dosage of 7.5 mg/200gr BW/ day, 15mg/200gr BW/day,and 30 mg/200gr BW/day respectively through peroral administration for 14 days. The research used Completely Randoized Design (CRD) and the data was then analyzed by one way ANOVA (Analysis of Variance) followed by Duncan test with the significance of 0.5. The results show that the mahkota dewa pulp extract shows significant impact on capacitation and acrosome reaction of rat. P2 group shows the highest percentage capacitation significance the a mean of 30.00 ± 4.24 and 5.60 ± 0.89 for acrosome reaction percentage. Keywords: Phaleria macrocarpa pulp extrtact; capasitation; acrosome reaction; sperm potention